Elaboración de una propuesta para la implementación del subsistema de evaluación de impacto ambiental en la provincia de Cotopaxi - Ronquillo Cando, Galileo Vladimir (2013)
In Ecuador, in province of Cotopaxi there is a commercial activity that performs its population as incomes of working and living. They have a habit of to generate some interaction on natural resources, lay on the line the quality of human life, which is why it is essential that mechanisms are applied to the prevention and control of pollution. One of the mechanisms that encompass the full applicability of policies, strategies and environmental regulations in a specific jurisdiction is commissioning of a Subsystem Environmental Management which are done by an official Environmental Authority Application as responsible (EAA) that can regulate and control those business activities that generate environmental impacts. The present investigation aims to design a Sub-Environmental Management System proposal has a few aspects which are described below….